2013
DOI: 10.12955/ejbe.v8i3.403
|View full text |Cite
|
Sign up to set email alerts
|

Does Productivity Matter in the Adoption of Hybrid Rice? A Comparative Study

Abstract: The present study was designed to analyze comparative economics of hybrid rice and basmati in the core rice growing area of Punjab. Cross-data was collected through well-structured questionnaires from 80 farmers during May and June 2011.Study results reveal that higher yield and less time required for maturity in production were the main reasons for planting of hybrid rice. Hybrid rice occupied 3.6 acres whereas area under basmati was 5.9 acres of the total farm area. Farmers obtained above 60 percent increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…In case of non-adopters, it was observed that (Table 2), the poor cooking quality of hybrid rice was the major problem. Similar findings by Saeed et al, (2013) reported that the disadoption of hybrid rice was due to serious problem of marketing and lower price and also disliking of hybrid rice due to poor quality of grain and inferior taste. High cost of seed which was also needed to be purchased every year, low price of the hybrid rice per quintal compared to other rice varieties, overlooking the higher production, infestation of the pest and disease were also among the reported problems.…”
Section: Problems Faced By Hybrid Rice Adopter and Non-adoptersupporting
confidence: 68%
“…In case of non-adopters, it was observed that (Table 2), the poor cooking quality of hybrid rice was the major problem. Similar findings by Saeed et al, (2013) reported that the disadoption of hybrid rice was due to serious problem of marketing and lower price and also disliking of hybrid rice due to poor quality of grain and inferior taste. High cost of seed which was also needed to be purchased every year, low price of the hybrid rice per quintal compared to other rice varieties, overlooking the higher production, infestation of the pest and disease were also among the reported problems.…”
Section: Problems Faced By Hybrid Rice Adopter and Non-adoptersupporting
confidence: 68%